To the ravines! Encountering, exploring, and expanding Toronto's mountain bike trails during and beyond the Covid-19 pandemic - Matthew Tiessen (SHARE Press, 2022)
This paper is about how Toronto's urban mountain bike trails offered an escape from the reductive worldview I'm calling the "Covid Cosmology". I describe how in the face of Covid-19 lockdowns, Toronto's mountain bike trails offer cyclists salutary experiences that run counter to those offered by the centralized authorities intent on managing the pandemic. These salutary experiences include: 1) Freedom; 2) Expansion, Optimization & Intensification, 3) Flow, 4) Boundaries, Exclusions, and Creating Community, and 5) Risk. Informed by non-representational ethnographic approaches (Vannini, 2015), I examine the use and expansion of Toronto's urban mountain bike trails by venturing into the wilds that exist above, below, and alongside urban environments during the pandemic's painful periods of lockdowns. The objective: to speculate about the ways human potential can be expanded with the help of urban wilderness and in response to totalizing ontologies designed to define life itself using a narrow, binaristic worldview.